Kinetic Characteristics of Electron Drift in Gas Discharge Plasma (International Journal of Mathematics and Physics, 2013)
An electron drift in a monatomic gas was studied for a spatially uniform electric field.Functions of the electron energy distribution are found by solving the Boltzmann equation in the two-termapproximation and applying the Monte Carlo method. We take into account both elastic and non-elasticcollisions of electrons with atoms, recombination at the walls. Integral characteristics of the electron driftin the gas were calculated, allowing to analyze the drift of electrons on a qualitative level. The results ofcalculations of the energy balance of electrons and drift characteristics in argon are shown at the values ofreduced field 1